INFILTRATION of SHIA: SEGMENTATION of AL-DAKHIIL in INTREPRETATION of AL-MISHBAH - Afrizal Nur (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2015)
M.Quraish Shihab is the Indonesian contemporary Muffassir, since he is capable and too bold to convey the message of the Qur’an that’s contextualized with the current situation which makes him popular, but at the same time his popularity started dropping as his pro-Shia views and interpretation, this has caused controversy among public. Shia infiltration is a segmentation of al-Dakhiil in the interpretation of the Koran, which is about the following issues: the cult of the Prophet Muhammad’s daughter (Fatima ra), Ali bin Abi Talib ra is First People who substitute the Prophet, believer in verse 105 of al-Tawbah letter are special people and Ahlul Bait. Among criticisms, there were always directed to the professor in Qur’an Tafseer at UIN Syarif Hidayatullah Jakarta is a rational interpretation in some cases above, because it is so memorable to his figures of contemporary Shi’ism. Hopefully, this article is as an effort to repair and may contribute to restore al-tafseer book of Mishbah commentary be dignified and highvalue tafseer equivalent to the works of previous commentary of Indonesian Mufassir